Development of the approach to proving the security of block ciphers to impossible differential attack - Ruzhentsev, Victor; Onishchenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2017)
Trends in the development of symmetric cryptography are constantly associated with the increasing of the sizes of keys and blocks. Block ciphers, which are used today in hashing algorithms, usually have a block size of 512 or 1024 bits. One of the main requirements for symmetric crypto algorithms is to provide resistance to known cryptanalytical attacks. Known methods of security estimation against impossible differential attack have too high complexity for such block sizes. The proposed approach for proving the absence of impossible differentials is applicable to some types of block ciphers and allows proving theoretically the resistance to impossible differentials attack. Rijndael-like SPN ciphers and Feistel ciphers are analyzed. For the group of Rijndael-like ciphers, the absence of byte impossible differentials for 4 or more rounds is proved. For the group of Feistel ciphers, the absence of byte impossible differentials for 6 or more rounds is proved. The first statement made it possible to prove the absence of byte impossible differentials for 4 or more rounds of the cipher Kalyna (DSTU 7624: 2014) with all block sizes, for 512-bit block ciphers that are used in the hash functions Whirlpool, Groestl and Kupyna (DSTU 7564: 2014). The second statement was used to prove the absence of byte impossible differentials for 6 or more rounds of Tornado and Labyrinth ciphers with a block size of 128 bits. Computational experiments on the impossible differentials search for these reduced models confirmed the validity of the obtained theoretical conclusions